2012
DOI: 10.1620/tjem.228.229
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Decrease of the Retinal Vasculature Area Identified with a Novel Computer-Aided Analysis System

Abstract: Fundus photographs enable non-invasive analysis of the status of the microcirculation by directly observing the retinal vasculature. Retinal microvascular abnormalities are important clinical markers of hypertension and arteriosclerosis, but retinal microvascular changes can be observed in older individuals without hypertension. In this study, our goal is to elucidate the effects of aging on fundus vessels in the retinal photograph. We analyzed retinal vessels of 161 healthy volunteers (49.5 ± 18.7 years, rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…SL density was found to be significantly higher in the older donor eyes, independent of the DL vascular density. This was an unexpected finding, as quite a few studies have identified an age-related decrease in retinal vasculature area, 40 ganglion cell layer Vessel density is expressed as percentage 6 SD; n value in parentheses indicates the number of measurements included in the calculation of mean value. thickness, 38 reduction in ganglion cell density, and rod photoreceptor cell 37 and rod bipolar cell density 41 with aging.…”
Section: Discussionmentioning
confidence: 89%
“…SL density was found to be significantly higher in the older donor eyes, independent of the DL vascular density. This was an unexpected finding, as quite a few studies have identified an age-related decrease in retinal vasculature area, 40 ganglion cell layer Vessel density is expressed as percentage 6 SD; n value in parentheses indicates the number of measurements included in the calculation of mean value. thickness, 38 reduction in ganglion cell density, and rod photoreceptor cell 37 and rod bipolar cell density 41 with aging.…”
Section: Discussionmentioning
confidence: 89%
“…Although older patients have higher blood pressure and arterial hypertension is more frequent in the elderly, the multiple linear regression analysis only identified the preexistent arterial hypertension as an independent determinant of PVD small vessels . Several experimental and clinical studies showed an agerelated worsening in microvascular flow in liver [25], cerebral cortex [25], retina [45], and cochlea [40]. Conflicting findings, however, have been described in other territories.…”
Section: Discussionmentioning
confidence: 98%
“…The alterations include reductions in luminal diameter [32], vascular density [4], and RBCV small vessels [30]. In hypertensive patients, several studies showed decreased capillary density in dermis [2][3][4] muscle [28], conjunctiva [41], and retina [45]. This is the first study that assessed the effects of chronic arterial hypertension on sublingual microcirculation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations